MANAGEMENT DEVELOPMENT TO POWERS OF THE PRODUCTION CAPITAL FUND OF THE BUILDING ENTERPRISE - A. G. Magomedov; M. Z. Zeynalov (Вестник Дагестанского государственного технического университета: Технические науки)
In article are considered problems of the estimation and management development to powers of the main fund of the building enterprise. It is conducted critical analysis of the ways of the estimation to powers of the main fund, offered different author, and on this base is improved way, connected with choice leading link. The offered methods, allowing adjust the structure of the main fund of the building enterprise with provision for available beside it building technology.